Seasonal changes in fitness parameters in a World Champion rowing crew - Mikulic, P. (International Journal of Sports Physiology and Performance, 2012)
Purpose: To examine variations in physical, physiological, and performance parameters over an annual train- ing cycle in a world champion rowing crew. Methods: Four world-class rowers, all of them members of the men`s heavyweight quadruple sculls squad who are current world rowing champions, were assessed 3 times at regular 4-mo intervals during the 2011 season (November 2010, March 2011, and July 2011). Physical assessments included stature, body mass, body composition, whereas physiological and performance assessments obtained during an incremental rowing ergometer test to exhaustion included maximum oxygen uptake and anaerobic gas-exchange threshold with corresponding power output values. Results: Body mass (~95 kg) and body composition (~12% body fat) remained stable over the annual training cycle. Power output at anaerobic gas-exchange threshold increased +16% from November to July, whereas the corresponding oxygen uptake, expressed as a percentage of maximum oxygen uptake, increased from 83% to 90%. Maximum oxygen uptake decreased from 6.68 L/min in November to 6.10 L/min in March before rising to 6.51 L/min in July. The cor- responding power output increased steadily from 450 W to 481 W. Conclusion: Seasonal variation in body mass and body composition of 4 examined world-class rowers was minimal. Oxygen uptake and power output corresponding to anaerobic threshold continuously increased from off-season to peak competition season. Seasonal variation in maximum oxygen uptake reached ~10%; however, it remained above 6 L/min, that is, the value consistently observed in top caliber heavyweight rowers regardless of the time of the assessment.